French arms exports the business of sovereignty - Beraud-Sudreau, Lucie (Adelphi (Series) (International Institute for Strategic Studies), 2020)
From De Gaulle onwards, France's strategic independence has been predicated on self-sufficiency in modern weapons. To achieve and maintain the requisite defence-industrial base, in the context of limited domestic orders, Paris sought to promote the export of its arms. During the Cold War, this underpinned but was also an expression of France's determination to resist bipolar domination. France offered customers around the world an alternative to reliance on one superpower or the other; and in doing so it generated the revenue to support an extensive domestic arms industry. The end of the Cold War ushered in fundamental changes, however: Western defence spending shrank and the global market was turned upside down. While France's arms-export policy was less affected by human-rights concerns than other democracies, it was not immune to pressures stemming from the consolidation of Europe's defence-industrial base and the increased interest of the EU in regulating the arms trade. This Adelphi book considers how France has responded to changing political and market circumstances in the way that it promotes and controls the export of weapons. It examines the rationale for considering a liberal arms-export policy as essential to French independence, and the institutional arrangements that underpinned this. It tracks the dramatic changes in the global arms market since 1990, in terms of demand and market competition, and charts the response of the French government to these changes. The book underlines how the French machinery of government, as a directing force behind the defence industry, has been resistant to the notion of export restraint - even in the case of sales to authoritarian regimes. However, it argues that France now faces a dilemma over whether to continue with a long-successful course, or to moderate its independence through greater collaboration to bolster European integration and better compete globally.